(3GdEYLGR GdJQHhj hGdfaSj aj GdbQBf hGdSfI GdeWgQIs - (3GdYjShj, YHO GdQMef eMeOs ((3HjQhJs (3OGQ GdfgVI GdYQHjIs, 2007)
(3JJejR GdJQHjI GdESdGejI HCfgG JYfi HLSe GdEfSGf hYbdg hfaSjJg hhLOGfg hVejQg hgj JQHjI eSJeQI eJhGUdI JhGcH GdaQO GdeSde ef GdegO Edi GddMO hJhGcHg aj cd eQGMd MjGJg hgj hEf cGfJ TehdjI ZjQ CfgG JQcR Ydi GdLGfH GdQhMj hGdEjeGfj hGdYbGFOj hGdCNdGbj, ceG CfgG JQHjI hGbYjI JQGYj XQha GdYUQ heJZjQGJg hEecGfGJg(B. (3hjecf GdfXQ defGgL GdESdGe Ch CSGdjHg aj HfGA TNUjI GdaQO GdeSde Ydi CfgG JTed GdJcGed Hjf GdfXQ hGdJWHjb hbO JYQV HYV GdcJGH dfhGM eMOOI ef efGgL GdJQHjI GdESdGejI(B. (3EdG Cf eDda gPG GdcJGH (B"(3GdEYLGR GdJQHhj hGdfaSj aj GdbQBf GdcQje hGdSfI GdeWgQI(B" (3jYQV HTcd efgLj eaUd dcd eaQOGJ heXGgQ gPG GdEYLGR EP jHjf cja jecf GdGSJYGfI HGdYde aj JYOjd hJZjjQ fahS GdfGS hSdhcge hMKge Ydi GdGSJbGeI hGdWGYI hGdhdGA ddg JYGdi hdQShdg GdcQje(B. (3jbY GdcJGH aj SJI aUhd(B: (3JMOK GdaUd GdChd Yf Jchjf GdVejQ GdCNdGbj MjK jYQV hLgI fXQ GdYde GdMOjK Yf cjajI Jchjf GdVejQ GdCNdGbj hJfejJg(B. (3bHd Cf jYQV ddefgL GdESdGej aj Jchjf GdVejQ GdCNdGbj(B. (3haj GdaUd GdKGfj jSJYQV GdeDda Cge GdeaGgje GdfaSjI hGdWH faSjI aj GdbQBf GdcQje hGdJj cGf dg aUd GdSHb aj EOQGcgG bHd GdYdhe GdMOjKI aj GdfaS hGdWH GdfaSj hGdJQHjI hGdGLJeGY(B. (3hjYQV GdeDda cPdc aj GdaUd GdKGdK ddCeQGV GdfaSjI GdCcKQ GfJTGQkG hTjhYkG(B. (3ceG jYQV GdaUd GdQGHY defGgL GdYdGL GdfaSj GdMOjK, djYQV ajeG HYO GdaUd GdNGeS deHGOF GdYdGL GdfaSj GdESdGej EP jHjf Cf GdESdGe cdg OYhI EUdGMjI YdGLjI EfSGfjI EjLGHjI JUdM GdaQO hGdeLJeY Ydi MO ShGA(B. (3aGdESdGe eOQSI aj GdWH GdYbdj hGdGLJeGYj heOQSI NdbjI LGeYI JfXe MjGI GdaQO hMjGI GdLeGYI ceG jYQV CNjQkG GdaUd GdSGOS dCKQ GdgOi GdESdGej aj YdGL GdGcJFGH hGdhbGjI efg(B.s
(3GdfhY (B: (3cJGHs
Keywords: Education religieuse; Religious education; (3GdJQHjI GdOjfjIs